MANIFESTASI IDEOLOGI ROMANTIK DALAM PUISI-PUISI ACEP ZAMZAM NOOR - Nita Widiati Efsa (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe the romantic ideology manifestation in Acep ZamzamNoor’s poems, in terms of: (a) romantic feelings, (b) romantic nature, (c) romanticimagination, and (d) romantic mythology. The data sources were ten poetry anthologiesby Acep Zamzam Noor (AZN) that were published in 1982-2007. The data analysis stepswere: (a) reading and checking the selected data, (b) marking and classifying data, and (c)analyzing data based on relevant theories, namely those of new historicism, archeologicalknowledge, and psychology of religion. The research findings are as follows. First, theromantic ideology manifestation related to feelings comprises: (a) longing, (b) loneliness,(c) anxiety, and (d) death. Second, the romantic ideology manifestation related to natureincludes: (a) sea, (b) mountain, and (c) sky. Third, the romantic ideology manifestationrelated to imagination comprises: (a) production imagination and (b) reproductionimagination. Fourth, the romantic ideology manifestation related to mythology includes:(a) religious myth, (b) ritual myth, (c) historical myth, (d) erotic myth, and (e) politicalmyth.Keywords: ideology manifestation, romantic ideology, feelings, nature, imagination,mythology